O trabalho das (os) assistentes sociais na Universidade Federal do Paraná nos períodos mais afetos da pandemia da Covid-19 no Brasil (2020-2022) - Neres, Ivanice de Oliveira Candido (2024)
In this study, the central theme is the professional work of social workers during the most crit-ical periods of the Covid-19 pandemic in Brazil (2020-2022), focusing on the socio-occupational space of Social Work at the Federal University of Paraná (UFPR), specifically the professionals working in the Pro-Rectory of Student Affairs and the Psychosocial Support Units across the institution's campuses. The research sought to answer the following guiding question: To what extent did the pandemic deteriorate and make the work of social workers in higher education at UFPR more flexible during the 2020-2022 period, and have these changes been overcome or do they persist in the socio-occupational space?The research has the general objective of analyzing the professional work of social workers at UFPR in the context of changes brought about by the Covid-19 pandemic (SARS-CoV-2) between 2020 and 2022. This goal unfolds into the following specific objectives:I) Investigate the impacts of the pan-demic on the working relationships in Social Work in Brazil; II) Understand the impacts of the pandemic on the work of social workers at UFPR, as well as their challenges in the face of changes during the 2020-2022 pandemic period;III) Examine whether the changes caused during the pandemic in the professional work of social workers at UFPR persist or have been overcome.To achieve and develop the methodological approach, the study employed qualita-tive, exploratory research, incorporating consultations, bibliographic and documental analysis, using UFPR’s publicly available institutional documents, as well as national decrees and regu-lations issued during the Covid-19 pandemic. The field research utilized semi-structured inter-views conducted through an online questionnaire directed at professional social workers.The study presents reflections on the reality experienced by professionals during the pandemic, characterized by a context of challenges requiring struggles and dialogues to implement the political-professional project of Social Work within higher education. Additionally, based on data collection and field research with the participation of professionals, the pandemic context revealed a period of intensified flexibilization and precarization of social workers' labor rela-tions in higher education. This context brought about changes that altered daily professional routines, marked by increased workload, abrupt adjustments to service flows, challenges with digital platforms for work execution, among other transformations. These changes, as outlined in this dissertation, have not yet been overcome, as revealed by the conducted investigation.